The Use of First Language (L1) in EFL Classrooms: Teachers’ Practices and Perspectives - Sundari, Hanna; Febriyanti, Rina Husnaini (International Journal of Education, 2021)
Teaching English in the context of foreign language needs vigorous efforts and strong commitment, especially for non-native English-speaking teachers to maintain professionalism and to achieve the success of learning language. Generally, it is believed that a teacher should be a language model for the learners by providing a great deal of input in the target language and applying the L2 only policy. However, some teachers finally decide to use their first language (L1) or mix it with the target language (L2) while teaching. This qualitative study investigated the frequencies, functions, and teachers’ perceptions of their L1 use in EFL classes. Twenty English teachers from lower secondary schools in Jakarta, Indonesia were asked to participate. The data were collected through classroom observations, in-depth interviews, and focus group discussions. The finding obtained that the frequency of the L1 was seemingly noticeable but not overused. Moreover, teachers used first language mostly for activity objective, translation, comprehension check, and activity instruction. The finding also revealed that the majority of the teachers decided to mix first language and target language with different proportions. Meanwhile, the others decided to use a small portion of target language. Only few teachers consistently tried to instruct mostly in target language. The finding implies the need for teachers to reduce the usage of first language (L1) during the teaching process to get maximal result.